ETHNOMATHEMATICAL PRACTICES AND THEIR INFLUENCE ON ELEMENTARY LEARNERS’ NUMERICAL LITERACY: A QUASI-EXPERIMENTAL STUDY - Sinta Verawati Dewi; Hery Saputra; Nurina Happy (International Journal of Teaching and Learning, 2025)
This quasi-experimental study investigates the impact of ethnomathematical practices integrated into the Realistic Mathematics Education (RME) model on the numerical literacy of elementary students in Tasikmalaya, Indonesia. The research addresses the persistent issue of low numeracy skills among Indonesian students, as evidenced by national assessments and international benchmarks such as PISA. A total of 59 fifth-grade students were selected through cluster random sampling from SD Negeri Kasturi and divided into control and experimental groups. The experimental group received instruction using an RME model enriched with local cultural contexts, while the control group followed conventional methods. Data collection instruments included validated questionnaires and observation sheets, with analysis conducted through normality and homogeneity testing, followed by independent t-tests. Results indicated a statistically significant difference in post-test scores, with the experimental group outperforming the control group (t = 2.931 > tₜ = 2.771). Observational data further revealed increased student engagement and participation in culturally contextualized learning activities. The findings suggest that integrating ethnomathematics into instruction enhances students' numerical literacy by providing relevant, engaging, and meaningful learning experiences. This study contributes to the discourse on culturally responsive pedagogy and offers practical implications for curriculum development in diverse educational settings.